Lipoxygenase activity and browning formation of lychee in syrup after high pressure and canning processes - P. Chaikham (2018)
This study aimed to evaluate the effect of high pressure (200, 400 and 600 MPa at 25°C for 10 and 20 min) and canning (100°C for 18 min) processes on lipoxygenase (LOX) activity and browning formation of lychee in syrup. Results showed that the pH profile of LOX activity in lychee was bell-shaped with a maximum activity around pH 4.0. After pressurization, the activities of LOX in lychee flesh apparently diminished with the increasing the pressure levels and processing times, in particular at a pressure of 600 MPa for 10 and 20 min the decreases in activity were 86% and 89%, respectively. For lychee in syrup, LOX was completely inactivated in canned sample, whereas the residual activities in pressurized batches as treated at 200-600 MPa for 20 min were ranged of 18-88%. In addition, pressurized samples depicted much lower browning index than that canned product, since heated lychee extract resulted in the pink color formation with a maximum absorption at 544 nm.